Moi, je, moi-même : l’altérité dans les champions du box-office du cinéma - Martins, Ana Tais (2021)
This work aims to reflect on the symbolic conditions (Durand, Bachelard) that, in cinema, can take part of the image of success. This, considered in its requirements of consensus and collective adhesion, is defined from the premise of the Imaginary Studies on the representations of the logical principles of antithesis, analogy and complexity, pondering that the relation with difference is fundamental to understanding the symbolic condition of success. With this premise, three of the ten films considered the greatest box-office hits of all time are examined: Gone with the Wind, Avatar and Titanic. The paper concludes that in both Avatar and Titanic there is a dualistic approach to otherness, while in Gone with the Wind the approach is monistic. In either case, plurality is retracted, with the refusal of the Other's effectiveness as a third party.